Understanding the Nurse-Patient Interaction at Komfo Anokye Teaching Hospital. The Patients' Perspectives and Experiences - Mensah, O.N. (University of Ghana, 2013)
The nurse–patient interaction, a core of professional nursing practice, shows the relationship that exists between nurses and their patients in the care encounter. This study set out to explore and understand the experiences patients go through during their interactions with nurses and to find ways of enhancing nurse-patient interactions. The study took place at the maternity, adult medical and surgical wards of the Komfo Anokye Teaching Hospital (KATH), Kumasi, Ghana. The target population for this study was all patients who were admitted for a week or more and had come for review after discharge at the time of the study. A qualitative exploratory approach was adopted and purposive sampling technique was used to select the desired sample. A semi-structured interview guide was used to elicit information from 12 patients. The data was analyzed using content analysis. The key findings were: nurses were found to be poor communicators, nurses discriminated among patients based on patients‘ social status and ability to pay for services rendered which led to deliberate neglect of patients. Nurses‘ poor attitudes were found to have a negative influence on the nurse/patient interaction. Many nurses had little or no respect for the rights of patients. Supervision was found to be poor leading to patients‘ ill-treatment, especially on night shifts. A few nurses were however described as good, supportive and caring. The inclusion of interpersonal skills, especially communication skills in nursing curricula, in-service training and workshops was recommended to improve the quality nursing care delivery at KATH.
Thesis (MPhil) - University of Ghana, 2013